Finite group actions on products of spheres - Daccach, J. A.; Vieira, João Peres [UNESP] (Springer, 1996)
In this work we make some contributions to the theory of actions of finite groups on products of spheres. Suppose that the group Z(q)(tau) acts freely on the product of k copies of spheres. Question: Is r less than or equal to k? We solve this question for several values of r and k.